2019
DOI: 10.1007/s10231-019-00928-8
|View full text |Cite
|
Sign up to set email alerts
|

Variational characterizations of $$\xi $$-submanifolds in the Eulicdean space $${{\mathbb {R}}}^{m+p}$$

Abstract: ξ-submanifold in the Euclidean space R m+p is a natural extension of the concept of selfshrinker to the mean curvature flow in R m+p . It is also a generalization of the λ-hypersurface defined by Q.-M. Cheng et al to arbitrary codimensions. In this paper, some characterizations for ξ-submanifolds are established. First, it is shown that a submanifold in R m+p is a ξ-submanifold if and only if its modified mean curvature is parallel when viewed as a submanifold in the Gaussian space (R m+p , e − |x| 2 m ·, · );… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The λ -hypersurfaces can be characterized as having constant weighted mean curvatureH = e − |X| 2 2nH , whereH is the mean curvature of M n in Gaussian metric space. As Li and Li [10] pointed out, if self-shrinkers and λ -hypersurfaces take the places of minimal submanifolds and hypersurfaces with constant mean curvature, respectively, then ξ -submanifolds are expected to take the place of submanifolds with parallel mean curvature vector. Therefore, the research of ξ -submanifolds is interesting and significant.…”
Section: Cheng and Weimentioning
confidence: 99%
See 4 more Smart Citations
“…The λ -hypersurfaces can be characterized as having constant weighted mean curvatureH = e − |X| 2 2nH , whereH is the mean curvature of M n in Gaussian metric space. As Li and Li [10] pointed out, if self-shrinkers and λ -hypersurfaces take the places of minimal submanifolds and hypersurfaces with constant mean curvature, respectively, then ξ -submanifolds are expected to take the place of submanifolds with parallel mean curvature vector. Therefore, the research of ξ -submanifolds is interesting and significant.…”
Section: Cheng and Weimentioning
confidence: 99%
“…In 2016, Li and Chang [9] derived a rigidity theorem for Lagrangian ξ -submanifolds in the complex 2-plane C 2 . Li and Li [10] gave some characterizations for ξ -submanifolds. They showed that a submanifold in R m+p is a ξ -submanifold if and only if its modified mean curvatureH = e − |X| 2 2nH is parallel when it is viewed as a submanifold in the Gaussian space (R n+p , e − |x| 2 n δ AB ) .…”
Section: Cheng and Weimentioning
confidence: 99%
See 3 more Smart Citations